Calcium efflux pump, PMCA2, in human breast tissue with lactational change and as a therapeutic target in breast cancer. Issue 2 (January 2015) - Peters, Amelia A.; Lee, Wei C.; Dray, Eloise; Smart, Chanel E.; Reid, Lynne; da Silva, Leonard; Lakhani, Sunil R.; Roberts-Thomson, Sarah J.; Monteith, Gregory R.
Abstract: Calcium pumps and channels modulate cell proliferation and apoptosis by regulating intracellular calcium (Ca2+). The plasma membrane Ca2+ ATPase isoform, PMCA2, is a calcium efflux mechanism that extrudes Ca2+ from the cytosol into the extracellular space. PMCA2 has a restricted expression, including expression in cochlear hair cells and cerebellar Purkinje cells. PMCA2 expression is increased in mouse mammary glands during lactation where it plays a major role in the excretion of Ca2+ into milk; however, PMCA2 expression has not been assessed in human breast tissue exhibiting lactational changes. Our previous studies have shown that PMCA2 mRNA levels are elevated in some breast cancer cell lines and that pan-PMCA antisense attenuates the proliferation of MCF-7 breast cancer cells. However, the consequences of silencing PMCA2 in breast cancer cells are still not well understood. Our study assessed PMCA2 expression in breast tissue exhibiting lactational change and in human malignant breast tissue samples. The role of PMCA2 in the proliferation of breast cancer cells was also evaluated. Immunohistochemistry using a rabbit anti-PMCA2 antibody showed membranous PMCA2 expression in the luminal epithelium of breast tissue exhibiting lactational change. PMCA2 expression was assessed in human breast tumor samples assembled into tissue microarrays. Nine of 96 breast tumours (9.4%) showed membranous PMCA2 staining. PMCA2 expression did not significantly correlate with the breast cancer pathological markers, estrogen, progesterone or HER2 receptor status. High-content imaging demonstrated that PMCA2 silencing in MDA-MB-231 breast cancer cells is associated with a reduction in cell number and an inhibition of the percentage of S-phase positive cells. The effect of PMCA2 silencing combined with various cytotoxics (cisplatin, doxorubicin or mitomycin C) on cell proliferation was assessed in MDA-MB-231 cells using a kinetic imaging system (IncuCyte). The results showed that PMCA2 silencing promotes the effects of some cytotoxics. These findings indicate that PMCA2 protein expression is elevated during human lactation and in some breast cancers. Inhibitors of PMCA2 may represent a novel therapeutic strategy for some breast cancers.